Gamma sensory entrainment for cognitive improvement in neurodegenerative diseases: opportunities and challenges ahead - Sahu, Prangya Parimita; Tseng, Philip (Frontiers in Integrative Neuroscience, 2023)
Neural oscillations have been categorized into various frequency bands that are mechanistically associated with different cognitive functions. Specifically, the gamma band frequency is widely implicated to be involved in a wide range of cognitive processes. As such, decreased gamma oscillation has been associated with cognitive declines in neurological diseases, such as memory dysfunction in Alzheimer’s disease (AD). Recently, studies have attempted to artificially induce gamma oscillations by using 40 Hz sensory entrainment stimulation. These studies reported attenuation of amyloid load, hyper-phosphorylation of tau protein, and improvement in overall cognition in both AD patients and mouse models. In this review, we discuss the advancements in the use of sensory stimulation in animal models of AD and as a therapeutic strategy in AD patients. We also discuss future opportunities, as well as challenges, for using such strategies in other neurodegenerative and neuropsychiatric diseases.